Inserción laboral femenina en el cantón Shushufindi provincia de Sucumbíos - Moreira Muñoz, Selena Jirley ,Rivadeneira Salazar, Alexander Fabian (2024)
ABSTRACT: This research work begins with the identification of the determinants of female labor insertion in the Shushufindi canton. For its execution, the quantitative approach and descriptive research with the survey technique were used, carrying out 338 surveys aimed at women in the canton. Job insertion was selected as the dependent variable and age, ethnicity, marital status, head of household, children, educational level, work experience, income level and cultural factors as independent variables based on their choice on a bibliographic review for the correct application of the Logit model and Probit. It was identified which of the independent variables are significant: income level, work experience, ethnicity, and educational level. Also, it was determined a model choice under various selection parameters such as the log likelihood, which demonstrates which model best fits the data, as well as the Akaike and Bayesian information selection criterion, and the interpretation of the R2. The importance of considering relevant aspects such as the educational level is emphasized, since it is the core for women to enter the labor market, obtain experience, generate income in their homes, and climb the career ladder, achieving equality and leaving aside the marked labor segmentation that has been evidenced by the independent variables with significance.